Communication and information technologies annual politics, participation, and production - Robinson, Laura; Cotten, Sheila R.; Schulz, Jeremy (Bingley, U.K. : Emerald, 2015)
Sponsored by the Communication and Information Technologies Section of the American Sociological Association, this volume brings together nine studies of the digital public sphere. The contributions illuminate three key areas of digital citizenship, namely political engagement, participation networks, and content production. In the first section, authors address relationships including: new media and efficacy, YouTube and young voters, political interest and online news. In the following section, the contributions speak to the importance of participation in social, scholarly, familial, and support networks. Subsequently, in section three on production, two contributions offers insight into unequal production, more specifically, gendered digital production inequalities and the varied responsiveness of microbloggers to different kinds of media events and issues. As a whole, the contributions revisit old questions and answer important new queries about netizenship and the digital public sphere.
Political efficacy on the internet : a media system dependency approach / Katherine Ognyanova, Sandra J. Ball-Rokeach -- Engaging young voters in the political process : U.S. presidential debates and YouTube / Pamela Jo Brubaker, Michael Horning, Christopher M. Toula -- Generating political interest with online news / Shelley Boulianne -- Do social network sites increase, decrease, or supplement the maintenance of social ties? / Randy Lynn, James C. Witte -- How far can scholarly networks go? Examining the relationships between distance, disciplines, motivations, and clusters / Guang Ying Mo, Zack Hayat, Barry Wellman -- Family social networks, reciprocal socialization and the adoption of social media by baby boomer and silent generation women / Nancy Horak Randall, Sue Carroll Pauley, Aaron B. Culley -- To know that you are not alone : the effect of internet usage on LGBT youth's social capital / Robert T. Cserni, Ilan Talmud -- The gendered digital production gap : inequalities of affluence / Jen Schradie -- Event vs. issue : Twitter reflections of major news, a case study / Chris J. Vargo, Ekaterina Basilaia, Donald Lewis Shaw.
Print version record
Keywords: Social Science -- Media Studies; Social Science -- Sociology -- General; Media studies; Social interaction; Sociology; Communication -- Technological innovations; Communication -- Social aspects